Coexpression of ESBL, Amp C and MBL in gram negative bacilli - Kolhapure, Ruturaj M.; Kumar, Ashwin; Rajkumar, HRV (International Journal of Research in Medical Sciences, 2017)
Background: Resistant bacteria are emerging worldwide as a threat to the favourable outcome of common infections in community and hospital settings. Extended Spectrum Beta-Lactamases (ESBLs), AmpC β lactamases and Metallo-β Lactamases (MBL) are the three important mechanism of resistance to beta lactam drugs in the bacteria. The objective of the study was to screen gram negative isolates for co-expression of extended spectrum β-lactamase, Amp C β-lactamase and Metallo β-lactamase production. Methods: In this study 50 (27 male & 23 female) adult skulls were investigated to determine the type of asterion, its distance from important bony landmarks and also the nearby venous sinuses were measured. Results: Seven hundred and six isolates from various clinical samples from Kamineni institute of medical sciences Hospital, Narketpally, were processed during the period of October 2010 to September 2012. Gram negative bacilli were identified by colony morphology, gram stain, motility, enzyme detection tests, etc. ESBL detection was carried but by two procedures like double disc synergy tests (DDST) and phenotypic confirmatory disc diffusion test (PCDDT). AmpC Beta-lactamase detection was done by AmpC Disc Test. MBL production was tested by Imipenem-EDTA combined disc test. Conclusions: Klebsiella was the commonest isolate (28.47%) followed by E coli (26.48%), Pseudomonas aeruginosa (19.54%), Enterobacter (8.92%), Acinetobacter (8.92%) and Citrobacter (7.64%). A total of 272 out of 706 gram negative isolates were ESBL producers. ESBL production was seen more in E. coli followed by Klebsiella and P. aeruginosa. A total of 73 out of 706 isolates were inducible Amp C producers. AmpC production was seen more in Acinetobacter. A total of 65 out of 706 isolates were MBL producers. MBL Production was seen more in E. coli.